Prostate Histotripsy in an Anticoagulated Canine Model - Wheat, Jeffery C. (2009)
PURPOSE: Histotripsy is a non-invasive ultrasound technology which induces microbubble formation (cavitation) within tissues producing mechanical tissue fractionation. During initial in-vivo feasibility canine studies of prostate ablation, minimal hematuria was observed. In the current study, we sought to further explore this phenomenon by performing extensive prostate histotripsy treatments in anticoagulated canines. MATERIALS AND METHODS: Histotripsy was performed on 9 canine subjects pre-treated with 6 mg of oral warfarin for 3 to 5 days using an extracorporeal 750 kHz therapeutic ultrasound transducer delivering acoustic pulses to the prostatic urethra and periurethral parenchyma. After 7–28 days, the subjects were euthanized, transrectal prostate ultrasound was performed and the prostate was harvested. Serum hemoglobin and International Normalization Ratio (INR) were measured immediately prior to histotripsy treatment and at euthanasia. RESULTS: Mean treatment INR was 4.6 (median 2.4, range 1.2 to 11.3). There was no clinically significant change in hemoglobin concentration at euthanasia compared to baseline. At harvest, histologic sections of the prostate revealed a large cavity corresponding to the planned treatment volume incorporating the prostatic urethra and parenchyma in all subjects. Urine was clear within 2 days of treatment and no blood clots were seen. CONCLUSIONS: Despite therapeutic and supratherapeutic anticoagulation, histotripsy resulted in minimal bleeding despite significant fractionation and tissue debulking of the prostate. These results have prompted further studies to understand the mechanism of non-thermal hemostasis underlying histotripsy.